0
$\begingroup$

How can I see that the $\chi^2(n)$ random variable has the moment generating function $$(1-2t)^{-n/2}$$?

I would also like to know why precisely that if $Z \sim N(0,1)$ then $Z^2 \sim \chi^2(1)$.

And if $X_i \sim \chi^2(1)$ and the $X_i$ are independent then $\sum_{i=1}^n X_i \sim \chi^2(n)$.

Are these two last lines just the definition of $\chi^2$?

$\endgroup$
1
  • $\begingroup$ These are all well known facts that you should be able to verify yourself from definitions. Where exactly are you stuck? $\endgroup$ Feb 11 '18 at 18:43
1
$\begingroup$

Starting with your last questions first: yes, the $\chi^2$ distribution with $k$ degrees of freedom is normally defiined as being the sum of the squares of $k$ independent $N(0,1)$ distributions.

For the moment generating function, note that since the MGF of a sum of independent variables, is the product of the MGFs, if $M_k$ denotes the moment generating function of $\chi^2(k)$ then

$$M_k(s) = M_1(s)^k.$$

Then to derive $M_1(s)$, denoting $X = N(0,1)^2$ and $f$ for the pdf of a $N(0,1)$ variable

\begin{align*} M_1(s) & = \mathbf E \left[ e^{sX^2} \right] \\ & = \int_{-\infty}^\infty \exp(sx^2) f(x) dx \\ & = \frac{1}{\sqrt{2\pi}} \int_{-\infty}^\infty \exp\left(sx^2\right) \exp\left(-x^2/2\right) dx\\ & = \frac{1}{\sqrt{2\pi}} \int_{-\infty}^\infty \exp\left((s-1/2)x^2\right) dx\\ & = \frac{1}{\sqrt{2\pi}} \int_{-\infty}^\infty \exp\left(-\frac{x^2}{2 (1-2s)^{-1}}\right) dx\\ & = \frac{\sqrt{2 \pi (1-2s)^{-1}}}{\sqrt{2 \pi} }\\ & = \left(1 - 2s\right)^{-\frac12} \end{align*} where in the second to last line we used the fact that the integral is the un-normalized pdf of a $N\left(0, 1-2s \right)$ distribution.

From the above we then get $$ M_k(s) = M_1(s)^k = (1 - 2s)^{-k/2}.$$


Why is the MGF of a sum of independent variables the product of their MGFs?

This follows from the fact that given independent random variables $X,Y$ and functions $U,V$ then $$ \mathbf E [ U(X) V(Y)] = \mathbf E[U(X)] \mathbf E[V(Y)]$$ In the special case that $U_s(x) = V_s(x) = \exp(sx)$ then $$U_s(X)V_s(Y) = \exp(sX)\exp(sY) = \exp(s(X+Y)),$$ so the result about the MGFs follows.

To justify the general claim, we note that the joint distribution function of two independent variables satisfies $f_{X,Y}(x,y) = f_X(x)f_Y(y)$ and then

\begin{align*} E [ U(X) V(Y)] &= \int_{-\infty}^\infty \int_{-\infty}^\infty U(x) V(y) f_{X,Y}(x,y) dx dy \\ & = \int_{-\infty}^\infty \int_{-\infty}^\infty U(x) f_X(x) V(y)f_Y(y) dx dy \\ & = \int_{-\infty}^\infty U(x)f_X(x) \left(\int_{-\infty}^\infty V(y)f_Y(y)dy \right) dx \\ & = \int_{-\infty}^\infty U(x)f_X(x) \mathbf E[V(Y)] dx\\ & = \mathbf{E}[V(Y)] \int_{-\infty}^\infty U(x)f_X(x) dx\\ & = \mathbf E[V(Y)] \mathbf E[V(X)]\\ \end{align*}

$\endgroup$
1
  • $\begingroup$ I'll go line by line from your proof, but for now, can you prove/give intuition for me yet this: For the moment generating function, note that since the MGF of a sum of independent variables, is the product of the MGFs? $\endgroup$
    – user122424
    Feb 11 '18 at 18:20

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.